Struktur Paragraf Deduktif dalam Buku Teks Bahasa Indonesia Wahana Pengetahuan dan Implikasinya dalam Pembelajaran - Dwi Suciani Alkafisa; Mulyanto Widodo; Bambang Riadi (FKIP Universitas Lampung, 2018)
This study aims to describe the structure of a deductive paragraph that is parallel in pattern, the structure of a deductive paragraph that has a chain pattern and the structure of a deductive paragraph that has a combination pattern in Indonesian textbooks for knowledge of SMP/MTs students of class VIII Bandar Lampung Published by the Ministry of Education and Culture. The method used is qualitative descriptive method. The data source used is 98 paragraphs in Indonesian textbooks. Based on the results of the study note that the results showed that the use of parallel deductive paragraph structure variations amounted to 40 uses, the structure of serial deductive paragraph structure amounted to 30 uses, deductive paragraph structure variations in combination of 25 uses, deductive paragraph structure variations of two total use and results based findings, structure of new deducible paragraphs consisting of topic sentences and only have one direct developer sentence, totaling 1 usage.Penelitian ini bertujuan untuk mendeskripsikan struktur paragraf deduktif yang berpola sejajar, struktur paragraf deduktif yang berpola berantai dan struktur paragraf deduktif yang berpola kombinasi dalam buku teks bahasa Indonesia wahana pengetahuan siswa SMP/MTs kelas VIII Bandar Lampung Terbitan Kemendikbud. Metode yang digunakan adalah metode deskriptif kualitatif. Berdasarkan hasil penelitian diketahui bahwa hasil penelitian menunjukkan bahwa penggunaan variasi struktur paragraf deduktif sejajar berjumlah 40 penggunaan, variasi struktur paragraf deduktif berantai berjumlah 30 penggunaan, variasi struktur paragraf deduktif kombinasi satu berjumlah 25 penggunaan, variasi struktur paragraf deduktif kombinasi dua berjumlah 2 penggunaan dan berdasarkan hasil temuan, struktur paragraf dedukdif baru yang terdiri atas kalimat topik dan hanya memiliki satu kalimat pengembang langsung, yang berjumlah 1 penggunaan.Kata kunci: deduktif, paragraf, struktur